Legal Risks in Co-Working Spaces and Consumer Protection Challenges in Custody Agreements and Cybersecurity - Amelia Firdausa Duana; Septian Oloan Sihombing; Ashari Ashari; Hetiyasari Hetiyasari (APPTHI, 2024)
This study examines the legal challenges and gaps in consumer protection related to custody agreements in co-working spaces in Indonesia. With the growing popularity of co-working spaces, consumers face significant issues such as the burden of proof in cases of lost or stolen items, unreasonably low compensation limits, and a lack of awareness about their legal rights. Existing legal frameworks, including Law No. 8/1999 on Consumer Protection (UUPK) and the Indonesian Civil Code (KUHPerdata), provide basic consumer rights but fail to address emerging risks such as cybersecurity threats, data protection, and complex service contracts in the co-working space context. Through a normative legal research methodology, this study analyzes the adequacy of current laws and proposes specific reforms to enhance consumer protection. It recommends updates to the UUPK, including clear guidelines on physical and digital security, consumer contract transparency, and liability for loss or damage, particularly concerning digital goods. The study also suggests strengthening dispute resolution mechanisms, incorporating modern technologies like biometric identification and blockchain for improved security and transparency, and establishing industry-wide standards. Lastly, it emphasizes the importance of consumer education and advocacy to ensure that users are aware of their rights. By implementing these recommendations, Indonesia can ensure a more secure and equitable co-working space environment.